2018
DOI: 10.1002/bjs.10898
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance tumour regression grade and pathological correlates in patients with rectal cancer

Abstract: Patients with mrTRG1 without tumour spread may be suitable for TAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…More specifically, a 5-year OS rate was significantly different among the five mrTRG groups (100% for mrTRG 1, 92.7% for mrTRG 2, 89.6% for mrTRG 3, 80.0% for mrTRG 4, and 40.0% for mrTRG 5, respectively) ( p = 0.024) and between the two mrTRG groups (91.0% for good responders and 79.1% for poor responders) ( p = 0.010). Considering that reassessment of the tumor after neoadjuvant treatment is essential to enable optimized treatment for patients with locally advanced rectal cancer ( 3 27 28 ), our results seem to be promising. We thought that technological development such as high-resolution imaging in MRI and accumulated knowledge in rectal MRI to discriminate cellular component of tumor signal from fibrosis might attribute to this excellent performance of mrTRG.…”
Section: Discussionmentioning
confidence: 86%
“…More specifically, a 5-year OS rate was significantly different among the five mrTRG groups (100% for mrTRG 1, 92.7% for mrTRG 2, 89.6% for mrTRG 3, 80.0% for mrTRG 4, and 40.0% for mrTRG 5, respectively) ( p = 0.024) and between the two mrTRG groups (91.0% for good responders and 79.1% for poor responders) ( p = 0.010). Considering that reassessment of the tumor after neoadjuvant treatment is essential to enable optimized treatment for patients with locally advanced rectal cancer ( 3 27 28 ), our results seem to be promising. We thought that technological development such as high-resolution imaging in MRI and accumulated knowledge in rectal MRI to discriminate cellular component of tumor signal from fibrosis might attribute to this excellent performance of mrTRG.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent study, Nahas et al, 10 showed, in contrast to most studies, that the clinical and radiological criteria for the identification of pCR exhibit low sensitivity (18.2%), with only 5% of the patients exhibiting pCR. 10 More recent studies still show that an MRI has a moderate and even low degrees of accuracy, even when working with a larger number of patients, as demonstrated by JK Jang et al, 17 whom was in his article had a sampled 439 patients. 17 Another current limitation is the fact that there is no specific protocol for the determination of tumour regression rates with either magnetic resonance imaging or histopathological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…10 More recent studies still show that an MRI has a moderate and even low degrees of accuracy, even when working with a larger number of patients, as demonstrated by JK Jang et al, 17 whom was in his article had a sampled 439 patients. 17 Another current limitation is the fact that there is no specific protocol for the determination of tumour regression rates with either magnetic resonance imaging or histopathological analysis. This lack motivated the development of a specific questionnaire for the collection of these data, which were obtained retrospectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients in whom there has been a good response but not an apparent cCR, local transanal excision is an alternative to major resection. MRI can be useful in guiding patient selection for such treatments. However, the recently published GRECCAR 2 study, which used a composite endpoint of surgical complications and recurrence, failed to show a difference between the two approaches in this setting, suggesting that more prospective studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%